Global Economic Prospects, January 2010 : Crisis, Finance, and Growth - World Bank (World Bank, 2012)
The world economy is emerging from the throes of a historically deep and synchronized recession provoked by the bursting of a global financial bubble. The consequences of the initial bubble and the crisis have been felt in virtually every economy, whether or not it participated directly in the risky behaviors that precipitated the boom-and-bust cycle. And while growth rates have picked up, the depth of the recession means that it will take years before unemployment and spare capacity are reabsorbed. This year's global economic prospects examines the consequences of the crisis for both the short and medium term growth prospects of developing countries. It concludes that the crisis and the regulatory reaction to the financial excesses of the preceding several years may have lasting impacts on financial markets, raising borrowing costs and lowering levels of credit and international capital flows. As a result, the rate of growth of potential output in developing countries may be reduced by between 0.2 and 0.7 percentage points annually over the next five to seven years as economies adjust to tighter financial conditions. Overall, the level of potential output in developing countries could be reduced by between 3.4 and 8 percent over the long run, compared with its pre-crisis path. The report further finds that the very liquid conditions of the first half of the decade contributed to the expansion in credit available in developing countries and that this expansion was responsible for about 40 percent of the approximately 1.5 percentage point acceleration of the pace at which many developing-country economies could grow without generating significant inflation. While developing countries probably cannot reverse the expected tightening in international financial conditions, there is considerable scope for reducing domestic borrowing costs, or increasing productivity and thereby regaining the higher growth path that the crisis has derailed.